"Now you see them, now you don't" Impact of flexible work arrangements on intra-workgroup relations - Thorgeirsdottir, Thora (Cranfield University, 2013)
Interest in flexible work arrangements has proliferated in the last years, fuelled by technological advancements that allow people to work from anywhere at any time. This systematic literature review explores the impact of flexibility in time and place of work on intra-group relations and subsequent effects on group-level outcomes. Findings suggest that flexibility in place of work has positive effects on employee-supervisor relationships but negative effects on co-worker relationships. Although teleworkers remain well connected to their co-workers and overall workgroup communication does not appear to change, informal socialisation processes are affected. Knowledge sharing and creation is subsequently challenged. Furthermore, managers of mixed workgroups face issues of fairness and justice as well as challenges of creating and maintaining group cohesion when some of their employees are not always present. However, little is known of how flexibility in time of work impacts intra-group relations and group outcomes from groups containing flexible workers have not been explored. This paper therefore identifies significant gaps in the literature and presents opportunities for further research.
Keywords: Flexible work arrangements; telework; flexitime; co-workers; team; workgroups